Ectopia Cordis - Rahman, Md Hamidur; Hassan, Mahmuda; Chowdhury, Kona; Quddus, Abdul (Journal of Nepal Paediatric Society, 2016)
Ectopia Cordis is a rare congenital anomaly characterized by partial or complete displacement of the heart outside the thoracic cavity. Usually ectopiacordis is associated with other multiple anomalies and intra cardiac defects. The five main ectopic positions are adjacent to the thorax approximately 60%, abdominal is 15-30%, thoraco-abdominal is 7-18%, cervical is about 3% and least is the cervicothoracic. We are reporting a case of ectopiacordis of abdominal type. This is the first reported abdominal ectopia cordis case in Bangladesh.